1974
DOI: 10.1042/cs0460295
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Responses to Sustained Handgrip in Normal Subjects and in Patients with Diabetes Mellitus: A Test of Autonomic Function

Abstract: 1. The blood pressure and heart rate responses to static muscular exercise were measured in sixty normal subjects and 124 patients with diabetes mellitus, aged 25-54 years, during a standardized sustained handgrip test at 30% maximum voluntary contraction (MVC).2. The normal range of the response was established. Females had a smaller blood pressure rise than males, and their MVC was lower. In the normal subjects there was a significant correlation between the size of the MVC and the height of the blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
3
2

Year Published

1984
1984
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(106 citation statements)
references
References 9 publications
4
97
3
2
Order By: Relevance
“…Contrary to our initial hypothesis and the results of a previous study 9) , we observed that the MBP response during static HG exercise in patients with type 2 DM was comparable to that in control subjects, despite the attenuation in the muscle metaboreflex. Although the reason for this discrepancy is unclear, it is possible that the central command and/or the muscle mechanoreflex may be exaggerated to compensate for the attenuated muscle metaboreflex-induced pressor response.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Contrary to our initial hypothesis and the results of a previous study 9) , we observed that the MBP response during static HG exercise in patients with type 2 DM was comparable to that in control subjects, despite the attenuation in the muscle metaboreflex. Although the reason for this discrepancy is unclear, it is possible that the central command and/or the muscle mechanoreflex may be exaggerated to compensate for the attenuated muscle metaboreflex-induced pressor response.…”
Section: Discussioncontrasting
confidence: 57%
“…In order to maintain adequate perfusion of the exercising muscle under these conditions, it is necessary to significantly increase blood pressure (BP) by sympathetic vasoconstriction rather than increase of CO 5) . There is evidence that BP increases are lower in diabetic subjects during static exercise than in healthy subjects 9) , indicating that impaired BP control may lower performance capacity during static exercise. However, to date no study has evaluated the neural mechanisms responsible for impaired BP control during static exercise performed by subjects with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…For all the above tests, R-R intervals were derived from continuously recorded ECG. Sympathetic function was studied by measuring BP and HR responses to forearm isometric exercise (handgrip) at 30% of patients' maximum force for 2 min [18] and to cold pressor test, i.e. immersion of hand up to mid-forearm in melting ice for 2 min [ 19].…”
Section: Methodsmentioning
confidence: 99%
“…Most of these studies have described changes in the systemic autonomic system, varying from an orthosympathetic hyperactivity [5] to a parasympathetic hyperactivity [2,4,6]. In our study we used a standardised protocol [8] that explores mainly the parasympathetic cardiovascular system. Moreover, we performed two tests (SSR, PH) to assess orthosympathetic function.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen ECH patients (14 males, 3 females, mean age 36.2 years, range 22-55) underwent a series of vegetative tests (Table 1), according to Ewing's protocol [8], to evaluate parasympathetic cardiovascular responses: lying to standing test (LST), Valsalva manoeuvre (VM) and deep breathing test (DBT); we also performed two tests, sympathetic skin response (SSR) and measurement of postural changes of blood pressure (PH), to assess vasoactive sympathetic pathway. Each patient was studied during either the active or silent period.…”
Section: Methodsmentioning
confidence: 99%